Isotope‐labeled amyloid‐β does not transmit to the brain in a prion‐like manner after peripheral administration. (27th May 2022) - Brackhan, Mirjam; Calza, Giulio; Lundgren, Kristiina; Bascuñana, Pablo; Brüning, Thomas; Soliymani, Rabah; Kumar, Rakesh; Abelein, Axel; Baumann, Marc; Lalowski, Maciej; Pahnke, Jens
Abstract: Findings of early cerebral amyloid‐β deposition in mice after peripheral injection of amyloid‐β‐containing brain extracts, and in humans following cadaveric human growth hormone treatment raised concerns that amyloid‐β aggregates and possibly Alzheimer's disease may be transmissible between individuals. Yet, proof that Aβ actually reaches the brain from the peripheral injection site is lacking. Here, we use a proteomic approach combining stable isotope labeling of mammals and targeted mass spectrometry. Specifically, we generate 13 C‐isotope‐labeled brain extracts from mice expressing human amyloid‐β and track 13 C‐lysine‐labeled amyloid‐β after intraperitoneal administration into young amyloid precursor protein‐transgenic mice. We detect injected amyloid‐β in the liver and lymphoid tissues for up to 100 days. In contrast, injected 13 C‐lysine‐labeled amyloid‐β is not detectable in the brain whereas the mice incorporate 13 C‐lysine from the donor brain extracts into endogenous amyloid‐β. Using a highly sensitive and specific proteomic approach, we demonstrate that amyloid‐β does not reach the brain from the periphery. Our study argues against potential transmissibility of Alzheimer's disease while opening new avenues to uncover mechanisms of pathophysiological protein deposition. Synopsis: Stable isotope‐labeled, brain‐derived amyloid‐β does not enter the brain after peripheral injection into mice. These findings argue against transmissibility of amyloid‐β aggregates and consequently Alzheimer's disease between individuals. The earlier stable isotope labeling starts in APPtg mice, the lower is the amount of already generated insoluble Aβ that is not metabolized anymore, and the higher is the fraction of newly produced Aβ incorporating the label. Peripherally applied Aβ reaches the liver and lymphoid organs and declines over time. Aβ does not enter the brain from the periphery after intraperitoneal injection while labeled lysine from injected brain extracts is incorporated into endogenously produced Aβ. Abstract : Stable isotope‐labeled, brain‐derived amyloid‐β does not enter the brain after peripheral injection into mice. These findings argue against transmissibility of amyloid‐β aggregates and consequently Alzheimer's disease between individuals.